2002
DOI: 10.3168/jds.s0022-0302(02)74150-7
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Sources of Amino Acids for Milk Protein Synthesis in Goats at Two Stages of Lactation

Abstract: An arteriovenous technique, combined with a 30-h i.v. infusion of [5-(13)CH3]Met and [5,5,5-(2)H]Leu, was used to monitor mammary uptake of free amino acid (AA) and to estimate the proportion of casein synthesized from circulating peptides in goats in early and late lactation. At both stages, kinetics was performed on the last day of consecutive 5.5-d periods. The first period was an i.v. infusion of saline and the second an i.v. infusion of lysine (8.9 g/h) plus methionine (2 g/h). Net uptake of essential AA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Previous studies in goats and cows have reported that Arg, a semi-essential AA, plays important roles in the regulation of milk protein synthesis (Mabjeesh et al, 2002;Doepel and Lapierre, 2011). A recent study in bovine mammary epithelial cells (BMEC) also found the addition of Arg to growth medium promoted the synthesis of casein (Wang et al, 2014); similar results were also reported by Zhao et al (2018) in lactating dairy cows.…”
Section: Introductionsupporting
confidence: 57%
“…Previous studies in goats and cows have reported that Arg, a semi-essential AA, plays important roles in the regulation of milk protein synthesis (Mabjeesh et al, 2002;Doepel and Lapierre, 2011). A recent study in bovine mammary epithelial cells (BMEC) also found the addition of Arg to growth medium promoted the synthesis of casein (Wang et al, 2014); similar results were also reported by Zhao et al (2018) in lactating dairy cows.…”
Section: Introductionsupporting
confidence: 57%
“…In goats at early and late lactation, methionine, histidine, threonine, proline, and phenylalanine in milk protein output were not accounted for in estimates of uptake of free AA (Mabjeesh et al, 2002). An in vivo isotope kinetic technique was used to determine the sources of AA for milk protein synthesis in which a long-term (greater than 20 h) i.v.…”
Section: Peptides As a Source Of Aa For The Mammary Glandmentioning
confidence: 99%
“…As the raw materials of milk protein synthesis, some EAA (lysine, methionine, and histidine) elicit regulation on the synthesis of milk protein (Prizant and Barash, 2008;Kim and Wu, 2009). Recently, some studies revealed that Arg, a conditionally essential AA, also has some positive effects on the synthesis of milk protein (Mabjeesh et al, 2002;Doepel and Lapierre, 2011). Some recent studies (Chen et al, 2013;Wu et al, 2016) have demonstrated that the addition of Arg in culture medium increased casein protein synthesis in bovine mammary epithelial cells (BMEC).…”
Section: Introductionmentioning
confidence: 99%